Conditions for Textile Electrode Sensors to Monitor Cardiac Activity in Daily Life - Kim, Jae Kwan; Park, Sangin; Cho, Hyun-Seung; Yang, Jin-Hee; Lee, Soo-Hong; Lee, Jeong-Whan (대한전기학회, 2022)
This study determined the conditions for textile electrode sensors combined with a garment-type wearable platform to monitor daily cardiac activity. Six types of textile sensors were implemented by manipulating the size and configuration of textile electrodes. Each sensor was attached to a chest band to fabricate experimental garments, which were sequentially worn by ten healthy males. Their electrocardiogram (ECG) signals were measured using the modified Lead II method. We sampled ECG signals at 1 kHz using a Biopac ECG100 device. The signal power ratio of the ECG signals acquired from each electrode was calculated, and statistical analysis was performed. The results indicate that convex electrodes detect higher quality signals than flat electrodes. However, no significant difference was observed in the performance of cardiac activity acquisition in terms of electrode size. These results validate that the type of configuration, namely flat or convex, significantly impacts the performance of cardiac activity signal acquisition. Additionally, correlation coefficients, mean error, and Bland-Altman plots revealed a strong positive correlation, low mean error, and adequate agreement, respectively, between ECG and all textile sensors. The study's findings form the basis for implementing a wearable platform that integrates textile sensors with garments.